Tamae’ Agokng Cultural Heritage Center: Safeguarding Dayak Traditions in Kubu Raya - Maulingga Agusta; Syahrul Syah Sinaga (Journal of Public Representative and Society Provision, 2026)
The objective of this research is to analyze the role of the Tamae’ Agokng cultural heritage center as a sanctuary for tradition and the preservation of Dayak culture in Kubu Raya Regency. This study examines how the cultural house functions as a space for the preservation, education, and transmission of Dayak cultural values. A qualitative approach with a case study research design was employed. The qualitative method was selected to facilitate an in-depth analysis of Tamae’ Agokng’s significance as a hub for cultural conservation. Through this approach, the roles, activities, and meanings of the cultural house as enacted by cultural practitioners and the community can be understood contextually. Furthermore, this research provides essential information to the public and cultural observers regarding the existence of a dedicated cultural space in Kubu Raya Regency that ensures the sustainability of Dayak heritage.